Effect of Eco-label and Renewable Energy Projects Knowledge on Environmental Awareness for Elementary School Students - Safitri, Desy; Fahrurrozi, Fahrurrozi; Nurhasanah, Nina; Marini, Arita; Subandi, Oman Unju; Tadjuddin, Shafruddin; Wirasti, Murti Kusuma; Kasirah, Irah (International Journal of Energy Economics and Policy, 2022)
Recently, environmental awareness has been an essential element for environmental sustainability and need researchers’ focus. Thus, this study aims at finding out the effect of eco-label and renewable energy projects knowledge on environmental awareness for 409 sixth grade elementary school students in the Province of Jakarta. In this study, data collection used questionnaires with the analysis technique of the Structural Equation Model (SEM). The findings indicate that eco-label and new renewable energy projects predict student environmental awareness. Indicators involving environmentally informative instruments, environmentally friendly labels, and environmental protection stimulate eco-label. Indicators consisting of environmental practices, environmental attitudes, and noble values of sustainability support student environmental awareness. This study offered to use eco-label and new renewable energy projects to improve student ecological awareness for elementary school students in the Province of Jakarta.